Coalescence, Spreading, and Rebound of Two Water Droplets with Different Temperatures on a Superhydrophobic Surface - Xu, Hao (ACS Omega, 2019)
[Image: see text] This paper studied the coalescence, spreading, and rebound of two droplets with different temperatures on a superhydrophobic surface. When the temperature of the impacting droplet was the same as that of the stationary droplet, there was a large deformation of both droplets before the coalescence and the energy dissipation was also large. The coalescence happened at the time close to the maximum spreading. When the temperature of the impacting droplet increased, the deformation of both droplets became smaller before the coalescence and the coalescence happened at or even before the droplets started to spread. The energy dissipation and loss in the later situation is less than those in the previous case. The rebounding characteristics of the merged droplets were also found to be dependent on the temperature. There is an optimum temperature at which the merged droplets can rebound for more times due to the balance of energy loss and also the interaction of the merged droplets with the underlying superhydrophobic substrate. These findings may help further the fundamental understanding of droplet collision on a superhydrophobic surfaces and also offer an alternative strategy to remove droplets from the underlying surfaces for different industrial applications, including condensation heat transfer in steam power plants and phase-change-based thermal management systems.